New daily persistent headache: A systematic review and meta-analysis. (May 2023) - Cheema, Sanjay; Mehta, Dwij; Ray, Jason Charles; Hutton, Elspeth J; Matharu, Manjit Singh
Objective: To perform a systematic review and meta-analysis of the epidemiology, precipitants, phenotype, comorbidities, pathophysiology, treatment, and prognosis of primary new daily persistent headache. Methods: We searched PubMed/Medline, EMBASE, Cochrane, and clinicaltrials.gov until 31 December 2022. We included original research studies with any design with at least five participants with new daily persistent headache. We assessed risk of bias using National Institutes of Health Quality Assessment Tools. We used random-effects meta-analysis where suitable to calculate pooled estimates of proportions. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis compliant study is registered with PROSPERO (registration number CRD42022383561). Results: Forty-six studies met inclusion criteria, predominantly case series, including 2155 patients. In 67% (95% CI 57–77) of cases new daily persistent headache has a chronic migraine phenotype, however new daily persistent headache has been found to be less likely than chronic migraine to be associated with a family history of headache, have fewer associated migrainous symptoms, be less vulnerable to medication overuse, and respond less well to injectable and neuromodulatory treatments. Conclusions: New daily persistent headache is a well described, recognisable disorder, which requires further research into its pathophysiology and treatment. There is a lack of high-quality evidence and, until this exists, we recommend continuing to consider new daily persistent headache a distinct disorder.